Radiography Of The Paranasal Sinus With Maxial Sinusitis In North Sumatra-Medan University Hospital - Sidauruk, Juliana Lasniar; Tarigan, Liberti (Future Science / FSH-PH Publications, 2022)
Paranasal sinus radiography is an appropriate method for showing abnormalities in the paranasal sinuses and showing abnormalities in suspected Maxillary Sinusitis. The purpose of this examination is to determine the location and location of sinusitis by obtaining an optimal picture with radiographic examination of the paranasal sinuses. This research was conducted at the Radiology Installation of the University of North Sumatra-Medan Hospital. Using a general X-ray unit with an aircraft capacity of 1100 mA in February 2022 - May 2022, with a qualitative descriptive research type. To show the anatomical description and pathological abnormalities in the paranasal sinuses, especially maxillary sinuses, parietoacanthia (water's method) and lateral projections are used. The results of the examination showed that there was Sinusitis Maxillaris Sinistra and a suspected Sinusitis Ethmoidalis Sinistra.